A relação adulto-criança no livro II do Emílio de Rousseau - Lauxen, Leandro Oliveira (2016)
This essay discusses the articulation of the relationship between adult-child in book II of Emilio by Rousseau, considering the second childhood as part of their natural education project and phase in which there is the necessity of strengthening the body and refinement of the senses.We defend the position that such a relationship is based both in the tutor’s need to keep the student constantly in touch with the nature as well as to maintain a balanced posture, avoiding the extremes in strictness and leniency, meeting the true necessities of the child and refuting the artificial ones. The addressing of this issue is taken forward through an analytical-interpretative movement of rousseaunian theoretical production, specifically from book II of Emilio. We use bibliographical research, based on exegetical procedure, to interpret the theme and the main concepts involved in it. In the first chapter, we present conceptions of childhood and education present in the context of Rousseau, as well as its educational project that involves natural education and social education. In the second chapter, we focus on the second childhood as the age of nature focusing on the principles of natural education, the meaning of the concept of nature, natural education through strengthening the body and refinement of the senses, as well as the role of the senses in the natural education.In the third and final chapter we explore the adult-child relationship in the book of Emilio and we make it through the criticism of adult’s authoritarianism, explaining the needs of the child and adult care, presenting some reaches of rousseaunian approach about adult-child pedagogical relationship on second childhood.